-6(6n+5)=38-2n

Simple and best practice solution for -6(6n+5)=38-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(6n+5)=38-2n equation:


Simplifying
-6(6n + 5) = 38 + -2n

Reorder the terms:
-6(5 + 6n) = 38 + -2n
(5 * -6 + 6n * -6) = 38 + -2n
(-30 + -36n) = 38 + -2n

Solving
-30 + -36n = 38 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
-30 + -36n + 2n = 38 + -2n + 2n

Combine like terms: -36n + 2n = -34n
-30 + -34n = 38 + -2n + 2n

Combine like terms: -2n + 2n = 0
-30 + -34n = 38 + 0
-30 + -34n = 38

Add '30' to each side of the equation.
-30 + 30 + -34n = 38 + 30

Combine like terms: -30 + 30 = 0
0 + -34n = 38 + 30
-34n = 38 + 30

Combine like terms: 38 + 30 = 68
-34n = 68

Divide each side by '-34'.
n = -2

Simplifying
n = -2

See similar equations:

| 3u-9+2(2u+3)=-7(u+3) | | x^2+25x-444=0 | | 1.3z-0.7(z+13)=0.6(z+5) | | -6(6n+5)=38-2n | | x^2+25x-444=0 | | 2e^6x=5e^9x | | .3333333333333y=6 | | 1.3z-0.7(z+13)=0.6(z+5) | | 2e^6x=5e^9x | | 1.3z-0.7(z+13)=0.6(z+5) | | 0+.3333333333333333y=6 | | 0+.3333333333333333y=6 | | 1.3z-0.7(z+13)=0.6(z+5) | | 0+.3333333333333333y=6 | | -06r-0.12=18 | | 0+.3333333333333333y=6 | | -06r-0.12=18 | | 3-5(x+7)+8=4x-12x+2(x-3) | | .5x+0=6 | | 4(x+4y)(x-4y)= | | 2z-7=8 | | g(x)=9x-6 | | 4p+9=29 | | 24-x+x=24 | | -(8+y)=2y-8-y | | -2(7x-3)+9x=6+5(2x-1) | | 4t-0.07=-0.55 | | X^2+4x-y^2-6y-12=0 | | 4p+9=29 | | 4t-0.07=-0.55 | | -(8+y)=2y-8-y | | 6(7a+1)=132 |

Equations solver categories